2010
DOI: 10.4134/bkms.2010.47.4.675
|View full text |Cite
|
Sign up to set email alerts
|

Two Step Algorithm for Solving Regularized Generalized Mixed Variational Inequality Problem

Abstract: Abstract. In this paper, we consider a new class of regularized (nonconvex) generalized mixed variational inequality problems in real Hilbert space. We give the concepts of partially relaxed strongly mixed monotone and partially relaxed strongly θ-pseudomonotone mappings, which are extension of the concepts given by Xia and Ding [19], Noor [13] and Kazmi et al. [9]. Further we use the auxiliary principle technique to suggest a two-step iterative algorithm for solving regularized (nonconvex) generalized mixed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Every monotone with respect to is pseudomonotone with respect to but converse does not hold in general. Definition 3 is vector version of -pseudomonotonicity studied by Kazmi et al in [23,24].…”
Section: Definitionmentioning
confidence: 99%
“…Every monotone with respect to is pseudomonotone with respect to but converse does not hold in general. Definition 3 is vector version of -pseudomonotonicity studied by Kazmi et al in [23,24].…”
Section: Definitionmentioning
confidence: 99%
“…In recent years, Bounkhel et al [6], Moudafi [20], Wen [28], Kazmi et al [17], Noor [[23, 24, 22] and the relevant references cited therein], Alimohammady et al [1], Balooee et al [4] suggested and analyzed iterative algorithms for solving some classes (systems) of nonconvex variational inequality problems in the setting of uniformly prox-regular sets.…”
Section: Introductionmentioning
confidence: 99%